Development of West Syndrome in Infants with Epileptic Discharges - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
Of 45 infants having epileptic discharges on the EEG in early infancy, 26 developed West syndrome (WS), in a study at Okayama University, Japan.